Porphyromonas gingivalis Induces Proinflammatory Cytokine Expression Leading to Apoptotic Death through the Oxidative Stress/NF-κB Pathway in Brain Endothelial Cells - Vichuda Charoensaensuk (MDPI AG, 2021)
Porphyromonas gingivalis, a periodontal pathogen, has been proposed to cause blood vessel injury leading to cerebrovascular diseases such as stroke. Brain endothelial cells compose the blood-brain barrier that protects homeostasis of the central nervous system. However, whether P. gingivalis causes the death of endothelial cells and the underlying mechanisms remain unclear. This study aimed to investigate the impact and regulatory mechanisms of P. gingivalis infection in brain endothelial cells. We used bEnd.3 cells and primary mouse endothelial cells to assess the effects of P. gingivalis on endothelial cells. Our results showed that infection with live P. gingivalis, unlike heat-killed P. gingivalis, triggers brain endothelial cell death by inducing cell apoptosis. Moreover, P. gingivalis infection increased intracellular reactive oxygen species (ROS) production, activated NF-κB, and up-regulated the expression of IL-1β and TNF-α. Furthermore, N-acetyl-L-cysteine (NAC), a most frequently used antioxidant, treatment significantly reduced P. gingivalis-induced cell apoptosis and brain endothelial cell death. The enhancement of ROS production, NF-κB p65 activation, and proinflammatory cytokine expression was also attenuated by NAC treatment. The impact of P. gingivalis on brain endothelial cells was also confirmed using adult primary mouse brain endothelial cells (MBECs). In summary, our results showed that P. gingivalis up-regulates IL-1β and TNF-α protein expression, which consequently causes cell death of brain endothelial cells through the ROS/NF-κB pathway. Our results, together with the results of previous case-control studies and epidemiologic reports, strongly support the hypothesis that periodontal infection increases the risk of developing cerebrovascular disease.